1962
DOI: 10.1161/01.res.10.5.746
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cardiogenic Shock

Abstract: The acute hemodynamic changes that result from coronary embolization were studied in the intact dog. Coronary embolization with lycopodium spore suspension resulted in an immediate and marked decrease in cardiac output, hypotension to shock level, elevation of pulmonary arterial and left atrial pressures, and marked increase in total peripheral resistance. These profound hemodynamic responses were partially blocked in dogs previously atropinized. The therapeutic implications of the results were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1964
1964
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The problem whether reflexes emanating from the heart may play a role for the circulatory adjustments in connection with experimental coronary infarction has been extensively studied. Levy and Frankel (1953), Wegria et al (1954), Struppler (1957, Matthes (1962), Guzman et al (1962 found no evidence for a depressor reflex from the left ventricle during the coronary infarction. On the contrary, Agress et al (1957 a, b) described a depressor reflex with the afferent connections in the sympathetic nerves during coronary infarction in dogs, but these observations have not been confirmed by others.…”
Section: Discussionmentioning
confidence: 96%
“…The problem whether reflexes emanating from the heart may play a role for the circulatory adjustments in connection with experimental coronary infarction has been extensively studied. Levy and Frankel (1953), Wegria et al (1954), Struppler (1957, Matthes (1962), Guzman et al (1962 found no evidence for a depressor reflex from the left ventricle during the coronary infarction. On the contrary, Agress et al (1957 a, b) described a depressor reflex with the afferent connections in the sympathetic nerves during coronary infarction in dogs, but these observations have not been confirmed by others.…”
Section: Discussionmentioning
confidence: 96%
“…These findings agree with those of Agress et al 5 Aortic thermodilution curve from the same experiment as figure 1 recorded after plastic microspheres injected into the coronary arteries through an occluding aortic catheter. Guzman et al 2 also embolized the left anterior descending coronary artery by injecting lycopodium spores and noted a similarly diminished stroke output and systolic pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Using the same dose, concentration, and suspending medium, other authors have reported that the spores lodge singly or in aggregates of 3 to 10 in arterioles 40 to 500 a in diameter. 2 Detailed observations were not begun until 10 to 15 minutes after embolization so that any immediate reflex or transient vasomotor responses could subside. The experiment was stopped usually when a persistent arrhythmia began; this occurred after an average of 6.7 embolizations.…”
Section: Methodsmentioning
confidence: 99%
“…Nach den Untersuchungen von Metzger (19) (4,11,12,14,15,16,17,21,22) sowie der kardiogene Schock (13,20). Nach den Untersuchungen von Metzger (19) (4,11,12,14,15,16,17,21,22) sowie der kardiogene Schock (13,20).…”
Section: Diskussionunclassified